2002
DOI: 10.1046/j.1523-1747.2002.19634.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Survival, Differentiation, and Death: Many Roads Lead to Mitogen-Activated Protein Kinase

Abstract: The epidermis is a dynamic and continually renewing surface that provides and maintains a life-sustaining interface with the environment. The epidermal keratinocyte, the major cell type of the epidermis, undergoes a complex and carefully choreographed program of differentiation. This process requires a balance between keratinocyte proliferation, differentiation, and apoptosis. This overview will concentrate on cascades that regulate the balance between keratinocyte cell proliferation and survival, and apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 65 publications
7
103
1
2
Order By: Relevance
“…Activation of this cascade is associated with cessation of cell proliferation and increased morphological differentiation (8,10,15), and prolonged stimulation can cause apoptosis (4,8). Stimulation of MAPK activity by this cascade is not associated with changes in expression of p38␦ or ERK1/2 level but is associated with increased p38␦ activity and reduced ERK1/2 activity (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of this cascade is associated with cessation of cell proliferation and increased morphological differentiation (8,10,15), and prolonged stimulation can cause apoptosis (4,8). Stimulation of MAPK activity by this cascade is not associated with changes in expression of p38␦ or ERK1/2 level but is associated with increased p38␦ activity and reduced ERK1/2 activity (6).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced ERK activity is associated with survival, whereas enhanced p38␦ activity is associated with differentiation and apoptosis (4 -10). Three p38 isoforms, p38␣, p38␤, and p38␦, are expressed in keratinocytes (5,8). Among these, p38␦ has a key role as a positive regulator of keratinocyte differentiation (7).…”
mentioning
confidence: 99%
“…4). Dusp genes are negative regulators of MAPK signaling (25), and MAPK affects many aspects of keratinocyte differentiation and survival (26). Furthermore, Ancelin et al (27) found that Blimp-1 bound to dusp2, suggesting Blimp-1 may enhance MAPK signaling by repressing various dusp genes.…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this critical life-sustaining function, keratinocytes, the major cell type of the epidermis, undergo a tightly regulated terminal differentiation program, also known as cornification (reviewed in refs. [33][34][35][36][37][38]. During this process, mitotically active keratinocytes of the innermost basal layer withdraw from the cell cycle, detach from the underlying basement membrane, and progressively differentiate to form spinous, granular and cornified epidermal layers, as they ascend toward the skin surface to ultimately develop into squames, dead flattened anucleated cornified cells.…”
Section: The Role Of P38δ In Regulation Of Keratinocyte Functionmentioning
confidence: 99%